2015
DOI: 10.18632/oncotarget.5970
|View full text |Cite
|
Sign up to set email alerts
|

LINC00152 promotes proliferation in hepatocellular carcinoma by targeting EpCAM via the mTOR signaling pathway

Abstract: Hepatocellular carcinoma (HCC) is well known as the sixth most common malignant tumor and the third leading cause of cancer-related deaths globally. LINC00152 was documented as an important long non-coding RNA (lncRNA) involved in the pathogenesis of gastric cancer; however, the detailed mechanism of action of LINC00152 remains unknown. Here, based on the increased level of LINC00152 in HCC tissues, we found that LINC00152 could promote cell proliferation in vitro and tumor growth in vivo. Furthermore, microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 38 publications
9
141
1
Order By: Relevance
“…The lncRNA BANCR has been found to offer potential as a diagnostic marker of lung cancer (26), Zfas1 offers potential as a marker of breast cancer (27), and TUG1 offers potential as a diagnostic marker of bladder cancer (28). In addition, the lncRNAs PVT1 (29), HULC (30), HEIH (31), ATB (32), DANCR (33), and LINC00152 (34) have been found to be dys-regulated in conditions like HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA BANCR has been found to offer potential as a diagnostic marker of lung cancer (26), Zfas1 offers potential as a marker of breast cancer (27), and TUG1 offers potential as a diagnostic marker of bladder cancer (28). In addition, the lncRNAs PVT1 (29), HULC (30), HEIH (31), ATB (32), DANCR (33), and LINC00152 (34) have been found to be dys-regulated in conditions like HCC.…”
Section: Introductionmentioning
confidence: 99%
“…5C). A previous study showed that the promoter region of linc00152 was hypomethylated in hepatic carcinoma tissues than in para-cancer tissues via bisulfite sequencing polymerase chain reaction [22] (Fig. 5D).…”
Section: Resultsmentioning
confidence: 98%
“…(C) Linc00152 expression was inversely correlated with DNA methylation of the linc00152 locus in breast cancer in TCGA. Linc00152 was hypo-methylated in hepatic carcinoma tissues compared with para-cancer tissues via bisulfite sequencing polymerase chain reaction [22]. (E) DNA methylation in the linc00152 locus in pan-cancer tissues and that in normal tissues in 450K data from TCGA.…”
Section: Resultsmentioning
confidence: 99%
“…which causes activation of Phosphoinositide 3-kinase (PI3K)/AKT serine/threonine kinase (AKT) signaling (26). LINC00152 is involved in the oncogenesis of hepatocellular carcinoma by activating the mechanistic target of the rapamycin (mTOR) signaling pathway (27).…”
Section: Other Lncrnasmentioning
confidence: 99%